2006
DOI: 10.1136/jcp.2005.033035
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation characteristics of leucocytes can predict bacteraemia in critical care patients: Figure 1

Abstract: Background: Early detection of blood stream infection can be lifesaving, but the results of blood cultures are not usually available before 24 hours after blood sampling. An earlier indication would lead to the initiation of immediate and adequate antibiotic treatment with obvious advantages for the patient. Objective: To evaluate the ability of leucocyte count, serum procalcitonin (PCT) concentration, erythrocyte sedimentation rate (ESR), and leucocyte antisedimentation rate (LAR) in predicting the blood cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
1
15
0
5
Order By: Relevance
“…Other conventional laboratory signs of sepsis, such as lactate, blood glucose, or thrombocyte counts, which are sensitive and easy to measure, are also very nonspecific (148). For example, the commonly used laboratory parameter of leukocytosis has very low sensitivity and specificity for the diagnosis of infection, with a likelihood ratio of 1.5; band counts have a similarly low diagnostic accuracy (25,66,187). The diagnostic uncertainty may explain why physicians find it difficult to define the disease and to communicate about it with patients and relatives (232).…”
Section: Current Deficits and The Need For New Diagnostic Approaches mentioning
confidence: 99%
“…Other conventional laboratory signs of sepsis, such as lactate, blood glucose, or thrombocyte counts, which are sensitive and easy to measure, are also very nonspecific (148). For example, the commonly used laboratory parameter of leukocytosis has very low sensitivity and specificity for the diagnosis of infection, with a likelihood ratio of 1.5; band counts have a similarly low diagnostic accuracy (25,66,187). The diagnostic uncertainty may explain why physicians find it difficult to define the disease and to communicate about it with patients and relatives (232).…”
Section: Current Deficits and The Need For New Diagnostic Approaches mentioning
confidence: 99%
“…LAR was previously reported in the critical care setting as a novel method for detecting activation of circulating leucocytes that can be the earliest sign of systemic inflammatory response syndrome 22. Here, we found that an early activation of leucocytes occurs during acute cerebrovascular events, since patients with both definitive stroke and TIA had significantly higher LAR compared to healthy controls as early as 6 hours after the onset of symptoms.…”
Section: Discussionmentioning
confidence: 50%
“…LAR correlated significantly with serum procalcitonin (PCT) and C-reactive protein (CRP) concentration in critically ill patients with severe sepsis 21. The simple LAR test was a good positive predictor of bacteraemia in critically ill patients presenting their first febrile episode without preceding antibiotic treatment 22 23…”
mentioning
confidence: 98%
“…A Bonferroni correction was calculated for each group of comparisons. The number of patients required was calculated by power analysis according to LAR results from our previous study, performed on a similar population, in which a LAR greater by 15% (standard deviation 9%) showed a 91% sensitivity of predicting blood culture positivity [9]. With type I α = 5% and with type II (power) of 90%, we therefore needed 32 patients.…”
Section: Methodsmentioning
confidence: 99%